TOLERANCE OF PROBIOTIC BACTERIAL CANDIDATE FROM KAKAP PUTIH ON pH AND BILE SALT - Harjuni, Fiki; Mulyadi, Aras; ', Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The use of probiotic is one of alternatives to solve disease problem in aquaculture. This research aimed to examine tolerance of three lactic acid bacteria (KP1, KP2, and KP3) isolated from kakap putih (Lates calcarifer) toward pH and bile salt at different consentration. The bacterial isolates were enriched on MRS agar medium. Tolerance to pH was conducted in MRS broth at pH 3, 5 and 8. While, tolerance to bile salt were performed on MRS agar at consentration of 0, 0,1, 0,2, 0,3, and 0,4 %. Isolate KP3 at pH and incubated for 48 hours showed the highest tolerance, but the highest tolerance to bile salt was indicated by isolated KP2 at bile salt consentration of 0,3 %.Keyword: Tolerance, probiotic, Kakap Putih, pH, Bile Salt.